People's Views on Stereotypes of Pidie and Padang Communities - Amar Azizi (Winaya Inspirasi Nusantara Foundation, 2023)
This research aims to eliminate excessive negative assessments of a particular group or tribe before knowing and interacting with them directly. This research uses a descriptive-qualitative approach and obtains data by conducting interviews, observation, and documentation. This research uses symbolic interaction theory, which discusses some of the characteristics and processes of stereotype formation and also the factors that influence the existence of stereotypes against the Pidie and Padang communities. The results of this study show that most of the people of Banda Aceh do not judge the attitude of an individual in terms of ethnicity or the tribe where they come from. Instead, they see it directly from the person himself. Then most of them equally disagree or do not take issue with negative stereotypes about people from Pidie and Padang. In fact, they have their own stereotypes aimed at the people of Pidie and Padang, and the stereotypes are mostly positive stereotypes. The stereotypes of the people of Banda Aceh towards people from Pidie and Padang are inseparable from the interactions that occur in Banda Aceh City. In addition, stereotypes are also obtained from social environments such as family or close people. Stereotypes of negative views include people from Pidie and Padang being considered stingy, arrogant, chatty, stubborn, and selfish. However, there are also positive stereotypes, such as that people who come from Pidie and Padang are disciplined, not easily offended, frugal, good at trading, sociable, good at managing finances, persistent, enterprising, assertive, good at culinary, highly social, and have a good work ethic. The factors that influence the stereotypes of the people of Banda Aceh towards people from Pidie and Padang are not something that is brought about by birth but arise because they are learned from the social environment, perceptions, direct interaction, cultural elements, and mass media.